HIV-1 Tat recruits transcription elongation factors dispersed along a flexible AFF4 scaffold - Chou, Seemay (National Academy of Sciences, 2013)
The HIV-1 Tat protein stimulates viral gene expression by recruiting human transcription elongation complexes containing P-TEFb, AFF4, ELL2, and ENL or AF9 to the viral promoter, but the molecular organization of these complexes remains unknown. To establish the overall architecture of the HIV-1 Tat elongation complex, we mapped the binding sites that mediate complex assembly in vitro and in vivo. The AFF4 protein emerges as the central scaffold that recruits other factors through direct interactions with short hydrophobic regions along its structurally disordered axis. Direct binding partners CycT1, ELL2, and ENL or AF9 act as bridging components that link this complex to two major elongation factors, P-TEFb and the PAF complex. The unique scaffolding properties of AFF4 allow dynamic and flexible assembly of multiple elongation factors and connect the components not only to each other but also to a larger network of transcriptional regulators.